A Four-Year Retrospective Study on Epidemiology, Bacteriology, and Antimicrobial Resistance of Bacterial Isolates from Burn Wounds in a Tertiary Care Hospital - Shagufta Roohi1; Anjum Ara Mir1*; Tufail Ahmed1; Fakhri-Zehra Khaja1; Tabish Qayoom1; Nargis Bali1 (Journal of Medical Microbiology and Infectious Diseases)
Introduction: Burn wound infections are a significant cause of morbidity and mortality among burn patients. Understanding of the prevalent bacterial etiologies and their antimicrobial susceptibility patterns within a healthcare facility is crucial for optimizing management strategies. Methods: This retrospective descriptive study was conducted over a four-year period at the Department of Microbiology in a tertiary care facility. We analyzed swab and pus samples collected from burn wound patients admitted to the Department of Plastic Surgery. Demographic data, including age and gender, were collected. Positive bacterial cultures underwent Gram staining and culture for identification. Biochemical tests were used for species-level identification. Antimicrobial susceptibility testing was performed using the disk diffusion method according to CLSI guidelines. Statistical analyses were carried out using SPSS software version 23 employing the chi-square test. Results: Out of 750 swab and pus samples analysed, 556 (74.1%) yielded positive bacterial cultures. Gram-negative bacteria predominated, accounting for 475 (85.4%) isolates, while 81 (14.6%) were Gram-positive. The most prevalent pathogens were Pseudomonas aeruginosa (175, 31.47%), Klebsiella pneumoniae (100, 17.99%), and Acinetobacter baumannii (68, 12.23%). Notably, 80.5% of P. aeruginosa isolates exhibited multidrug resistance (MDR). Among Staphylococcus aureus isolates, 37 (72.7%) were methicillin-resistant (MRSA). Conclusions: Among all isolates, P. aeruginosa was the most prevalent bacterial pathogen. S. aureus was the most prevalent Gram-positive organism. 72.7% of S. aureus isolates were MRSA. The high prevalence of multidrug-resistant P. aeruginosa and MRSA underscores the importance of implementing an antimicrobial stewardship program guided by local antibiograms.